2008
DOI: 10.4103/0256-4947.51666
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress among male medical students in Egypt and Saudi Arabia : Effect of sociodemographic factors

Abstract: BACKGROUND AND OBJECTIVESIn Arab countries, epidemiological data about psychological morbidity among medical undergraduate students are scarce. This study sought to determine whether there was a difference in perceived stress levels of male medical students at Mansoura University, Egypt, compared with male medical students at King Faisal University, Saudi Arabia.METHODSThe sample consisted of 304 male medical students in Egypt and and 284 male medical students in Saudi Arabia. The self-reported questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
50
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 20 publications
14
50
3
Order By: Relevance
“…This study specifi ed that broken sleep and poor quality of sleep could be underlying causes of stress. [24] El-Gilany et al [25] evaluated effects of sociodemographic factors on medical students' stress and they confirmed that stress, anxiety and depression were all frequent among medical students. Another study was conducted on medical and dental students and concluded that work stress levels depended signifi cantly on the type of profession and time of work experience.…”
Section: Discussionmentioning
confidence: 98%
“…This study specifi ed that broken sleep and poor quality of sleep could be underlying causes of stress. [24] El-Gilany et al [25] evaluated effects of sociodemographic factors on medical students' stress and they confirmed that stress, anxiety and depression were all frequent among medical students. Another study was conducted on medical and dental students and concluded that work stress levels depended signifi cantly on the type of profession and time of work experience.…”
Section: Discussionmentioning
confidence: 98%
“…This result may be attributed to some factors that affect medical more than non-medical students like inappropriate teaching methods, poor learning environment and worry about failure which were commonly mentioned by medical more than non-medical students [5]. The stressors identified in one study were congested classrooms, troubles with teachers and fear of future [6]. Also, condensed academic courses, nationality (being non-Saudi) or having an emotional failure, all these make students more prone to anxiety and depression [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example; year one consists of (level 1 and level 2), year 2 consists of (level 3 and 4), year 3 consists of (level 5 and 6), year 4 consists of (year 7 and 8), and year 5 consists of level 9 [9]. Nursing students in Sau- According to the literature, nursing students in Saudi Arabia faces stress from their clinical environment's [3] [10] [11]. This negative experience, due to stress, can limit students learning and teaching and affect the overall quality of patient care [12].…”
Section: Bachelor Of Science In Nursing In Saudi Arabiamentioning
confidence: 99%